A companion of the generalised trapezoid inequality for functions of two variables with bounded variation and applications. (2016) - Budak, Hüseyin; Sarikaya, Mehmet Zeki
In this paper, a companion of trapezoid inequality for functions of two independent variables with bounded variation is established and some applications for general cubature formula are given.